THE CULTURAL COMPONENT IN TELETANDEM INTERACTIONS: THEORIES AND REFLECTIONS - Moretti, Giovana [UNESP]; Biondo Salomao, Ana Cristina [UNESP] (Unesp-faculdade Ciencias & Letras, 2019)
Teletandem Brasil: foreign languages for all is a project developed by UNESP with the aim of providing the learning of foreign languages by placing pairs of speakers of different languages in contact synchronously, in a collaborative way, through communication resources on the Internet (TELLES; VASSALLO, 2006). Based on previous research about the cultural components in this context, this article aims to present and reflect on the theoretical concepts about culture addressed in such research, in order to identify how how these concepts apply to the context of Teletandem, and how we can observe their presence in the participants' experience, both in interaction sessions and in subsequent mediations. We can conclude that this form of collaborative learning promotes the emergence of the cultural component dynamically among the participants as a process of reflection on their own language and culture provided by the interaction with the other.
Keywords: Telecollaboration; Foreign languages; Teletandem; Culture